Valvular heart disease: a companion to Braunwald's heart disease - Otto, Catherine M.; Bonow Robert O. (Philadelphia Elsevier/Saunders, 2014)
nternationally renowned cardiologists Drs. Catherine M. Otto and Robert O. Bonow help you to apply all of the latest scientific knowledge and clinical strategies with Valvular Heart Disease, a companion to Braunwald's Heart Disease. This indispensable resource for your everyday practice provides all of the knowledge you need to give your patients the most accurate diagnoses, the best possible heart disease treatment options, and the expert care they deserve. Consult this title on your favorite e-reader, conduc.